(untitled) (Tempo e Argumento, 2023)
This article has the film “Bacurau” as a possibility of use for teaching History starting form a dystopian time, to think a history of time in the present tense not disconnected front its past. We understand that these intersecting time dimensions can be worked on in teaching and learning practices based on the concept of historical literacy. Understanding the film’s plot as a cultural artifact, it is understood that, from its diverse narratives, times and spaces intersected by the inhabitants and outsiders of Bacurau, it is possible to identify and problematize the threads that lead to an understanding of historiographic concepts that favor historical learning based on the complexity of historical thinking and awareness for students in basic education. We understand these students as classroom partners who can share with each other and with the teacher previous knowledge identified in the practical life of the characters in the film and reflect on their own identities, the exercise of citizenship and the everyday experiences historically constituted to build new strategies for life and resistance to Eurocentric historical thinking that continues to colonize our bodies, minds and habits. It is expected that when working with the film, teachers and their classroom partners will assume the role of history researchers with a view to developing their own historical knowledge related to historical cognition.